User-Controlled Personal Assistance for Children—Does the Independent Living Ideology Translate to the Lived Life of Children and Youth with Disabilities? - Øyvind Ibrahim Marøy Snipstad; Stine Vik (Scandinavian Journal of Disability Research, 2023)
In Norway, user-controlled personal assistance (UPA) is a right for children under the age of 18. Based on the independent living (IL) ideology, the intention of UPA is to provide the person with user control, independence and more. However, in order to receive UPA, minors need an external actor to be formally in charge. Through a qualitative approach, this article discusses whether the ideological principles governing UPA can be utilised as intended in families where the parent is expected both to care for and protect the child as well as act as an administrator providing opportunities for the child to enjoy the IL principles. The findings in this article suggest that there may be a need to revise the ideological framework in order to better encompass the reality of childhood. Instead of full user control at present, UPA could be a viewed as an empowering tool in the process towards future independence.